Natural disinfectants against Candida albicans in partial and total dental prostheses - Guallpa , Kevin Michael (2024)
To determinate the efficacy of natural disinfectants against Candida Albicans in partial and total dental prostheses. This is a bibliographic review that focused on the search for scientific articles on disinfection of prostheses by natural methods on Scopus, SciELO and Google scholar databases. After applying the inclusion and exclusion criteria, 27 articles were selected that met the theoretical characteristics applicable to the research topic. Natural disinfectants such as mint, lemon verbena and thyme eliminate Candida albicans when exposed to concentrations of 50% for 24 hours, oregano is effective in concentrations less than 10% with the same exposure time, while muña demonstrates effectiveness in concentrations greater than 75%. The care and management of a prosthetic device is a priority, since the oral cavity is an ideal environment for the multiplication of microorganisms such as Candida albicans; It has been proven that when using mint, oregano, thyme, lemon verbena and muña with adequate concentrations they equal the action of medications such as fluconazole and doxycycline, limiting the reproduction of Candida albicans.